Jaguar (Panthera onca) food habits in Atlantic rain forest of southeastern Brazil - Garla, R. C.; Setz, EZF; Gobbi, N. (Associação Tropical Biology Inc, 2001)
Between January and December 1996, the food habits of a relict population of jaguars were studied in 220 km(2) Linhares Forest Preserve, which comprises much of the remaining old-growth Atlantic Forest of Espirito Santo, Brazil. Fecal analysis indicated opportunistic feeding on 24 prey species (N = 101 scats). Mammals represented 87 percent of the total items, followed by reptiles (9.8%) and birds (2.8%). Considering prey weight, 23.4 percent of the items weighed 1-3 kg, 40.5 percent were 3-10 kg, and 27.7 percent weighed more than 10 kg. Analysis of relative prey frequency and biomass indicated that the diet was concentrated in two prey types: long-nosed armadillo and white-lipped peccary. Literature data suggest that forest jaguars rely on the same mammal prey over their entire geographic range.
Keywords: Atlantic rain forest; Brazil; food habits; jaguars; Panthera onca; scat analysis